Statistical process control implementation in the food industry: A systematic review and implications for future research - Lim, Sarina; Antony, Jiju (Cranfield University Press, 2013)
This study is to illustrate a systematic review application in investigating common issues emerging from Statistical Process Control (SPC) implementation in the food industry. A total of 34 journal articles were rigorously selected from four databases and reviewed. The most common themes emerge in SPC implementation in the food industry is the benefits while the remaining themes are motivation, barriers and critical success factors (CSF). This review found that the evidence of SPC implementation in the food industry is beneficial; however, a lack of both awareness and guidelines relating to SPC implementation in the food industry has resulted in a slow adoption. This systematic review concluded that there is a crucial need for further research into the SPC deployment aspect addressing how to deploy SPC in the food industry in a systematic manner.
Keywords: Statistical Process Control; Food Industry; Systematic Review; Operation Management